Effect of dietary energy on digestibilities, rumen fermentation, urinary purine derivatives and serum metabolites in Tibetan and small‐tailed Han sheep. Issue 4 (25th April 2019) - Zhou, Jianwei; Wang, Wenji; Jing, Xiaoping; Degen, Allan; Guo, Yamin; Kang, Jingpeng; Shang, Zhanhuan; Yu, Zhongxiang; Qiu, Qiang; Guo, Xusheng; Ding, Luming; Yang, Guo; et al.
Abstract: Tibetan sheep are indigenous to the Qinghai–Tibetan Plateau, graze the grassland all year round without supplementation and are well‐adapted to the harsh conditions. Small‐tailed Han sheep were introduced to the plateau and are raised mainly in feedlots. Based on their different backgrounds, we hypothesized that the ability to cope with poor diets would be better in Tibetan than in Han sheep. To test our prediction, we examined the effect of dietary energy on apparent digestibilities, rumen fermentation, urinary purine derivatives and serum metabolites by using a 4 × 4 Latin square design in each sheep breed. Four diets were formulated to be low in crude protein ( 7%) but to differ in metabolizable energy concentration. Average daily gain was greater in Tibetan than in Han sheep ( p < 0.01) and increased linearly with an increase in energy intake ( p < 0.001). The digestibilities of dry matter, organic matter, gross energy, and neutral and acid detergent fibres were greater in Tibetan than in Han sheep ( p < 0.05). Ruminal pH was lower ( p < 0.05), while volatile fatty acids (VFAs), urea‐N, ammonia‐N and soluble protein‐N concentrations were higher ( p < 0.05) in Tibetan than in Han sheep. As a molar proportion of total VFA, acetate decreased ( p < 0.001) with an increase in dietary energy whereas propionate and butyrate increased ( p < 0.05). Urinary purine derivative excretion was greater in Tibetan than in Han sheep ( p < 0.01), as was microbial nitrogen production; both parameters increased with dietary energy ( p < 0.01). Serum concentrations of glucose, insulin and insulin‐like growth factor‐1 increased ( p < 0.05) as energy level increased, while non‐esterified fatty acids and growth hormone decreased ( p < 0.05). It was concluded that Tibetan sheep were better able to cope with low‐protein, low‐energy diets and, consequently, our prediction was supported.